1993
DOI: 10.1210/jc.76.3.690
|View full text |Cite
|
Sign up to set email alerts
|

The role of the sex-determining region Y gene in the etiology of 46,XX maleness

Abstract: The condition of 46,XX maleness is characterized by testicular development in subjects who have two X chromosomes but who lack a normal Y chromosome. Several etiologies have been proposed to explain 46,XX maleness: 1) translocation of the testis-determining factor from the Y to the X chromosome, 2) mutation in an autosomal or X chromosome gene which permits testicular determination in the absence of TDF, and 3) undetected mosaicism with a Y-bearing cell line. We evaluated 10 affected subjects who were ascertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 0 publications
3
59
0
4
Order By: Relevance
“…Molecular genetics analyses have demonstrated that approximately 90 % of these patients carry a variable amount of Y material due to a Y-to-X interchange caused by an illegitimate recombination during paternal meiosis [13][14][15]. There was a report of an XX male caused by a translocation of an SRY gene fragment from the Y chromosome to an autosome [16].…”
Section: Results Of Pcr and Fishmentioning
confidence: 99%
“…Molecular genetics analyses have demonstrated that approximately 90 % of these patients carry a variable amount of Y material due to a Y-to-X interchange caused by an illegitimate recombination during paternal meiosis [13][14][15]. There was a report of an XX male caused by a translocation of an SRY gene fragment from the Y chromosome to an autosome [16].…”
Section: Results Of Pcr and Fishmentioning
confidence: 99%
“…However, the great majority of the XX males with genital ambiguity are SRY negative [4,6]. Testing new Y-chromosome markers in XX males will make it possible to detect the breakpoints further in each individual and to establish correlations with the clinical features, identifying the Y regions implicated in the phenotypic definition.…”
Section: Discussionmentioning
confidence: 99%
“…On basis of the analysis and detection of SRY gene, 46, XX male patients can be clinically divided into SRY-positive and the SRY-negative groups (6,7). SRYpositive individuals usually have normal male genitalia, small azoospermic testes and hypergonadotropic hypogonadism (8), and most carry the SRY gene translocated to the X chromosome during paternal meiosis (7,9); however, SRY autosomal translocations have also been reported in some XX males (10)(11)(12). The diagnosis of SRY-positive patients is usually achieved in adulthood during infertility investigation (3).…”
Section: Introductionmentioning
confidence: 99%